PENGARUH FAMILY CONTROL, FIRM RISK, FIRM SIZE DAN FIRM AGE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA SEKTOR KEUANGAN - Lidia Hariyanto (Business Accounting Review, 2014)
This study aimed to examine the effect of family control, firm risk, firm size, and firm age on profitability and firm’s value. Samples were taken from 66 financial companies listed on the Indonesia Stock Exchange in the year of 2009-2011. This hypothesis was tested by using multiple linear regression. In this study, profitability measured by ROA (Return on Assets) and the value of the firm measured by Tobin’s Q. family control and firm risk had no affect on profitability and the value of the firm, while firm size had negative affect on profitability and positive affect on the firm’s value. Firm age had no affect on profitability but had negative affect on the firm’s value.